2001
DOI: 10.1176/appi.ajp.158.3.390
|View full text |Cite
|
Sign up to set email alerts
|

Limbic Responsiveness to Procaine in Cocaine-Addicted Subjects

Abstract: The pattern of hypoperfusion in the placebo state followed by heightened activation with procaine in the cocaine-addicted subjects is similar to the pattern of interictal hypoperfusion and ictal hyperperfusion that has been observed in subjects with epilepsy. The findings for the cocaine-addicted subjects may thus represent evidence of localized (orbitofrontal) sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 43 publications
3
51
1
2
Order By: Relevance
“…Recent work by Cooper et al (2006) suggests that the effect of cocaine on sodium channels in the subiculum may alter cocaine reinstatement. Both preclinical (DC Cooper et al, unpublished observation) and clinical (Adinoff et al, 2001) studies further suggest that neural activation by other sodium channel-mediated local anesthetics (ie procaine, lidocaine) is an attenuated effect following chronic cocaine administration. Thus, the effect of cocaine on cholinergic systems discussed below may be affected by non-dopaminergic processes, including a direct effect on ACh receptors.…”
Section: Non-dopaminergic Effects Of Cocaine On Achmentioning
confidence: 98%
“…Recent work by Cooper et al (2006) suggests that the effect of cocaine on sodium channels in the subiculum may alter cocaine reinstatement. Both preclinical (DC Cooper et al, unpublished observation) and clinical (Adinoff et al, 2001) studies further suggest that neural activation by other sodium channel-mediated local anesthetics (ie procaine, lidocaine) is an attenuated effect following chronic cocaine administration. Thus, the effect of cocaine on cholinergic systems discussed below may be affected by non-dopaminergic processes, including a direct effect on ACh receptors.…”
Section: Non-dopaminergic Effects Of Cocaine On Achmentioning
confidence: 98%
“…Therefore, in the current study we employ fMRI to characterize the functional significance of the abnormalities in the PFC of cocaine abusers that have been previously documented as decreases in metabolism, blood flow or volume (Adinoff B et al, 2001;Adinoff B et al, 2003;Goldstein R et al, 2004;Goldstein R and N Volkow, 2002;Kosten T et al, 2004;Volkow ND et al, 1992;Volkow ND et al, 1988). Since we have previously shown that the decreases in PFC metabolism (including ACG and orbitofrontal cortex) in cocaine abusers was associated with depressed DA D2 receptor availability, we propose that the putative PFC abnormalities reflect in part dopaminergic dysfunction (Volkow ND et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it has been used as an affective challenge in healthy volunteers (Ketter et al, 1996;ServanSchreiber et al, 1998), and patients with mood disorders (Ketter et al, 1993) and panic disorder , as well as in individuals abusing alcohol (George et al, 1990) and cocaine (Adinoff et al, 2001).…”
Section: Introductionmentioning
confidence: 99%